Data analytics and research evaluation. Issue 4 (31st May 2019) - Qiu, Lulu; Zhou, Elsie; Yu, Tiffany; Smyth, Neil
Abstract : Purpose: Librarians are challenged by technology transformations in research data metrics to re-position in the evolving cycles of research production, communication and evaluation. They are also are challenged by the new and emerging strategic needs of universities for data-driven research intelligence that provides a comparative edge in the global world of higher education. This paper aims to discover how libraries can support universities in applying international assessment standards by delivering new reference and information services based on data analytics. Design/methodology/approach: This paper focuses on a new reference and information service Research Data Analytics in China that was launched in 2017. There is a discussion of how new university needs have provided the strategic drive for librarians to develop skills. Findings: The Research Data Analytics service development is significant for showcasing a new role for librarians in relation to research data evaluation metrics linked to publication strategies for authors and strategic intelligence for institutions. This has driven the development of the library's position and influence in strategic research intelligence services. Originality/value: The future for librarians is about being adventurous. Librarians are experts who will sparkle and shine beyond the bubble of the library walls. They can demonstrate a commitment to supporting university colleagues in professional services and academia to blossom and flourish. Distinctive visual technologies can be adopted for exploring research data which transform research production, communication and evaluation and therefore transform our position and future through technology-enabled innovations.